2013
DOI: 10.3746/jkfn.2013.42.3.397
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment of the White-Spotted Flower Chafer (Protaetia brevitarsis) as an Ingredient for Novel Foods

Abstract: The pharmacological efficacy of Protaetia (P.) brevitarsis larvae has been described in the Dongui Bogam.It is believed that the larvae are particularly useful for hepatic disorders. However, natural aversion has made it difficult to consume these larvae as food. Thus, we sought to make an eatable form of the larvae by establishing optimal conditions for larvae preparation. Larvae were selectively bred, sterilized, and a powder of larvae generated by freeze-drying. Afterward, the CellTiter 96 ® AQueous Non-Rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
3

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 6 publications
0
8
0
3
Order By: Relevance
“…최근 국내에서는 곤충에 대한 관심이 높아지고 있으며 식품원료 및 의약용품 등에 대한 소재화 연구 등이 다수 진행되고 있다 (4)(5)(6). 식품의약품안전처의 식품공전에 등록 된 식용곤충은 벼메뚜기(Oxya japonica THUNBERG) 및 누에(Bombyx mori)가 있으며 (7), 가공제품 및 기능성 신소 재 등의 자원 활용방안에 대한 연구가 진행되고 있다 (8)(9)(10).…”
unclassified
“…최근 국내에서는 곤충에 대한 관심이 높아지고 있으며 식품원료 및 의약용품 등에 대한 소재화 연구 등이 다수 진행되고 있다 (4)(5)(6). 식품의약품안전처의 식품공전에 등록 된 식용곤충은 벼메뚜기(Oxya japonica THUNBERG) 및 누에(Bombyx mori)가 있으며 (7), 가공제품 및 기능성 신소 재 등의 자원 활용방안에 대한 연구가 진행되고 있다 (8)(9)(10).…”
unclassified
“…In Korea, the white-spotted flower chafer (P. b. seulensis) larva is known to have pharmacological activity in diseases such as hepatic disorders (Kwon et al, 2013). This insect is being reared artificially to meet the demand for this novel, functional food in Korea.…”
Section: )mentioning
confidence: 99%
“…Moreover, since the pretreatment conditions needed to utilize Pbl as a food ingredient were defined by Kwon et al . (), the Ministry of Food and Drug Safety (MFDS) approved its use as food from October 2014 onward. Pbl can now be manufactured and marketed as food in the Republic of Korea (Yoon et al .…”
Section: Introductionmentioning
confidence: 99%
“…According to the recent safety evaluations of Pbl's toxicity and content of harmful substances by Hwang et al (2001Hwang et al ( , 2007, Chung et al (2013), Jo et al (2008), Lee et al (2001b), Park et al (2012), and Noh et al (2015), no risk factors have yet been found in Pbl. Moreover, since the pretreatment conditions needed to utilize Pbl as a food ingredient were defined by Kwon et al (2013), the Ministry of Food and Drug Safety (MFDS) approved its use as food from October 2014 onward. Pbl can now be manufactured and marketed as food in the Republic of Korea (Yoon et al 2016).…”
Section: Introductionmentioning
confidence: 99%